PENERAPAN MEDIA PEMBELAJARAN KAHOOT UNTUK MENGURANGI KEBOSANAN BELAJAR SENI BUDAYA PADA SISWA KELAS X SMAN 8 DENPASAR - Gusti Ayu Made Puspawati; Dewa Ayu Widiasri; I Ketut Lanus (Widyadari, 2025)
Boredom in the learning process is often reflected in low student participation, which results in feelings of boredom, fatigue, lethargy, and lack of enthusiasm for learning. This study aims to examine the effectiveness of using Kahoot learning media in reducing boredom in learning the Art and Culture subject in class X students of SMAN 8 Denpasar. The method used is Classroom Action Research (CAR) which is carried out in two cycles, each consisting of planning, implementation, observation, and reflection stages. The results of the analysis showed that the average student boredom score decreased from the initial condition of 68.6 to 59.8 in cycle I, and then decreased again to 46.9 in cycle II. The decrease of 32% from cycle I to cycle II shows that the application of Kahoot as an interactive learning media is able to create a more interesting and enjoyable learning experience. The attractive visual characteristics and interactive features in Kahoot have been shown to increase student focus and engagement during the learning process. Thus, the use of technology and interactive media such as Kahoot can create a more dynamic and participatory learning atmosphere, and can increase students' enthusiasm for learning in the subject of Arts and Culture at SMAN 8 Denpasar.